Low-cost polyester-based degradable plastic garbage bag and its extrusion blow molding process
Patent Information
- Application Number
- CN202511446508.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-11
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2045-10-11
AI Technical Summary
[0006]本发明要解决的核心技术问题在于克服现有可生物降解塑料垃圾袋普遍存在的综合成本偏高、力学性能与使用体验不佳、降解行为可控性差以及加工过程稳定性不足等固有缺陷
1)低成本:通过采用价格较低的PBS作为主基体,并大量填充经改性的低成本纳米碳酸钙,显著降低了原料成本,提升了产品市场竞争力。
Smart Images

Figure CN121160046B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of polymer materials technology and plastics processing, and in particular to a low-cost, high-performance polyester biodegradable plastic garbage bag and its dedicated extrusion blow molding production process. Background Technology
[0002] Biodegradable plastic garbage bags, as an important product for combating "white pollution," have received widespread attention from all sectors of society because they can be decomposed into water, carbon dioxide, and biomass by microorganisms under specific environmental conditions after use. Among them, polyester biodegradable polymers, such as polybutylene succinate (PBS) and polylactic acid (PLA), are considered one of the ideal materials for making biodegradable garbage bags due to their good biocompatibility and biodegradability.
[0003] However, existing biodegradable garbage bags made from pure PBS, PLA, or simple blends thereof generally suffer from problems such as high overall cost, inferior mechanical properties and user experience compared to traditional polyethylene (PE) bags, poor controllability of degradation behavior, and narrow processing window. Specifically, firstly, the high price of pure PBS or PLA raw materials leads to high final product costs, making it difficult to promote on a large scale in the market to replace traditional PE bags; secondly, PLA material itself lacks toughness and is relatively brittle, making it prone to puncture or tearing when used as garbage bags, while PBS, although having better toughness, lacks strength and rigidity, and simple blending often fails to balance strength and toughness, resulting in unstable product mechanical properties and affecting user experience.
[0004] Current mainstream blow molding processes have significant technical limitations when processing such polyester materials: First, PBS and PLA are thermodynamically incompatible systems, and simple physical blending easily leads to phase separation, resulting in poor uniformity of the blown film, with obvious weaknesses or fisheyes, severely affecting the mechanical properties of the bag. Second, polyester materials are sensitive to hydrolysis. If the raw material pretreatment is insufficient, trace amounts of moisture can cause polymer molecular chains to hydrolyze and break during the high-temperature extrusion blow molding process, resulting in a significant decrease in melt strength and extremely poor film bubble stability, making it difficult to form ultra-thin, uniform films and resulting in low product yield. Third, existing processes often add large amounts of expensive compatibilizers or special additives to improve processability or performance, which further increases costs and may affect its final biodegradability. Fourth, the degradation control capability is insufficient; either degradation is too slow in the natural environment, losing the meaning of "biodegradable," or premature degradation occurs during storage or use, leading to performance degradation and failing to meet shelf-life requirements.
[0005] Furthermore, while existing technologies have attempted to reduce costs by adding inorganic fillers such as calcium carbonate, ordinary calcium carbonate has poor compatibility with the polyester matrix and an unreasonable particle size distribution. Excessive addition can lead to a sharp deterioration in the mechanical properties of the film and exacerbate screw wear during processing. In blow molding process control, improper matching of parameters such as temperature, blow-up ratio, and cooling efficiency can easily result in problems such as coarse film grains, poor transparency, stiff feel, or poor heat-sealing performance. Summary of the Invention
[0006] The core technical problem this invention aims to solve is to overcome the inherent defects of existing biodegradable plastic garbage bags, such as high overall cost, poor mechanical properties and user experience, poor controllability of degradation behavior, and insufficient stability in the processing. Traditional single polyester materials (such as pure PLA) are brittle and hard, while high-performance biodegradable materials (such as pure PBS) are expensive. Simple physical blending results in poor film uniformity and insufficient strength due to poor compatibility, making it difficult to meet the load-bearing and puncture resistance requirements of garbage bags. At the same time, existing processes are sensitive to the moisture content of raw materials and processing temperature, resulting in poor stability of blown film bubbles and low yield, further increasing production costs.
[0007] To address the aforementioned problems, this invention provides a method for manufacturing garbage bags based on low-cost polyester composite materials and a dedicated extrusion blow molding process. The core innovation of this method lies in the following: First, by using a PBS / PLA blend system with a specific ratio and introducing surface-modified nano-calcium carbonate as a reinforcing and compatibilizing agent, supplemented by the synergistic effect of transition metal salt degradation aids and maleic anhydride graft compatibilizers, a composite material system with low cost, controllable degradation characteristics, and excellent mechanical properties is constructed. Second, a single-screw extrusion blow molding process is designed, encompassing deep drying of raw materials, high-speed hot mixing, twin-screw melt blending and granulation, and a precise temperature control and internal cooling (IBC) system. This process effectively solves the hydrolysis and phase separation problems in polyester processing, ensuring the high stability of ultra-thin film formation.
[0008] Another objective of this invention is to provide a low-cost, biodegradable polyester-based plastic garbage bag prepared by the above method. This product not only significantly reduces raw material costs, but more importantly, it exhibits tensile strength, elongation at break, and right-angle tear strength comparable to traditional PE garbage bags, while also possessing the characteristic of rapid and complete biodegradation under controlled conditions, achieving a balance between performance and environmental friendliness.
[0009] Another objective of this invention is to provide applications for the aforementioned low-cost polyester biodegradable plastic garbage bags in daily and specific fields such as household waste collection, supermarket shopping, and agricultural covering. This aims to provide a reliable, large-scale alternative to single-use plastic products that truly achieves green end-of-life treatment in the context of "plastic restriction." Ultimately, through the organic combination of material innovation and process optimization, a reliable technical path is provided for the high-quality, low-cost production of biodegradable plastic products.
[0010] The objective of this invention is achieved through the following technical solution.
[0011] An extrusion blow molding process for low-cost polyester biodegradable plastic garbage bags includes the following steps: (1) Raw material pretreatment and drying: 50-70 parts by weight of polybutylene succinate (PBS) and 15-25 parts by weight of polylactic acid (PLA) were vacuum dried at 80-90℃ for 4-6 hours to reduce the moisture content of the material to below 200ppm; 10-20 parts by weight of nano-grade calcium carbonate that had been surface modified with silane coupling agent were dried at 110-120℃ for 2-3 hours for later use. (2) High-speed mixing: The dried PBS and PLA from step (1), modified nano-calcium carbonate, 0.5-2 parts by weight of transition metal salt compound as degradation aid, 0.5-2 parts by weight of maleic anhydride grafted polyester as compatibilizer, and 0.3-1 parts by weight of erucic acid amide opening agent are added to a high-speed mixer and mixed at 800-1200 rpm for 8-15 minutes at 60-80℃ to obtain a premixed uniform material; (3) Melt blending and extrusion: The premixed material obtained in step (2) is fed into a co-rotating parallel twin-screw extruder through a loss-in-weight feeder for melt blending and granulation. The temperature settings of each section of the twin-screw extruder from the feed port to the die head are as follows: Zone 1 150-160℃, Zone 2 160-170℃, Zone 3 170-175℃, Zone 4 175-180℃, Zone 5 175-180℃, the die head temperature is 170-175℃, the screw speed is 200-350 rpm, and the melt pressure is controlled at 3-6 MPa. After water cooling and pelletizing, biodegradable plastic masterbatch is obtained. (4) Blown film forming: The biodegradable plastic masterbatch obtained in step (3) is fed into a single-screw extruder blown film machine. The temperature of the single-screw extruder is set as follows: Zone 1 150-155℃, Zone 2 155-165℃, Zone 3 165-170℃, Zone 4 170-175℃, and the die temperature is 165-170℃. The melt is extruded through the annular die to form a tubular blank. Cooling air at 15-25℃ is injected into the film bubble. The film bubble inflation ratio is 2.5:1-3.5:1, and the traction speed is 15-25 m / min, thereby preparing a blown film with a thickness of 0.015-0.025 mm. (5) Post-processing and bag making: The blown film obtained in step (4) is stretched, flattened and corona treated. After the treatment strength is ≥38 dynes / cm, it is rolled into a film roll. Finally, the film roll is cut, heat-sealed and punched by a heat-sealing bag making machine to make the low-cost polyester biodegradable plastic garbage bag.
[0012] The above-mentioned process, through deep drying of raw materials and pretreatment of modified fillers, combined with a two-stage screw extrusion process and precise blown film temperature control and internal cooling system, synergistically solves the technical bottlenecks of easy hydrolysis, poor compatibility, and unstable film bubbles in polyester processing, achieving efficient and stable processing of low-cost biodegradable composite materials and the molding of high-performance ultrathin films. Furthermore, in the above-mentioned extrusion blow molding process, the weight ratio of polybutylene succinate (PBS) to polylactic acid (PLA) in step (1) is 60:20; the particle size D90 of the surface-modified nano-sized calcium carbonate is ≤ 2μm. This specific ratio effectively balances the toughness of PBS and the rigidity of PLA, while the ultrafine modified nanofiller plays a significant reinforcing and compatibilizing role, jointly ensuring the excellent comprehensive mechanical properties of the product.
[0013] Furthermore, in the above-mentioned extrusion blow molding process, the transition metal salt degradation aid mentioned in step (2) is one or a mixture of two of iron stearate and cobalt stearate; the compatibilizer is maleic anhydride-grafted polybutylene succinate PBS-g-MAH. Transition metal ions can catalyze the non-enzymatic hydrolysis of polyester molecular chains under composting conditions, thereby controlling the degradation rate; while PBS-g-MAH greatly improves the compatibility between PBS and PLA phases through interfacial coupling, preventing performance degradation.
[0014] Furthermore, in the above-mentioned extrusion blow molding process, the amount of erucamide-based opening agent added in step (2) is 0.5 parts by weight. This preferred addition amount ensures good opening properties while avoiding surface precipitation or poor heat sealing caused by excessive addition.
[0015] Furthermore, in the above-mentioned extrusion blow molding process, the screw length-to-diameter ratio (L / D) of the twin-screw extruder in step (3) is 40:1-48:1. A sufficient L / D ratio provides ample time for melting, shearing, mixing, and venting of the material, ensuring that all components, especially nanofillers and degradation aids, are highly uniformly dispersed in the matrix.
[0016] Furthermore, in the above-mentioned extrusion blow molding process, the blow-up ratio of the film bubble in step (4) is 3:1, and the thickness of the blown film is 0.020 mm. The blow-up ratio of 3:1 is an ideal choice to achieve a balance between the longitudinal and transverse mechanical properties of the film, while the thickness of 0.020 mm achieves the best balance between meeting the strength requirements and minimizing the raw material cost per bag.
[0017] This invention discloses a low-cost, biodegradable polyester plastic garbage bag, manufactured using any one of the extrusion blow molding processes described in 1 to 6 above. This garbage bag is a product of combining the innovative material formulation with a specialized processing technology, simultaneously achieving near-traditional PE bag performance, significantly reduced costs, and reliable complete biodegradability on a macroscopic scale.
[0018] Furthermore, the aforementioned low-cost polyester biodegradable plastic garbage bags possess a tensile strength ≥20MPa, an elongation at break ≥300%, and a right-angle tear strength ≥80kN / m. These quantitatively defined excellent mechanical properties ensure that the garbage bags have sufficient load-bearing capacity, impact resistance, and puncture resistance in actual use, providing a reliable user experience.
[0019] Furthermore, the aforementioned low-cost polyester biodegradable plastic garbage bags, under compostable conditions conforming to GB / T 20197-2024 standards, exhibit a biodegradability rate of ≥90% within 180 days. This characteristic ensures that the product can quickly and thoroughly return to nature in a specific environment after disposal, effectively avoiding "white pollution" and meeting both environmental policies and market demands. This invention further discloses the application of low-cost polyester biodegradable plastic garbage bags in household waste collection, supermarket shopping, or temporary covering of agricultural waste. With its reliable performance and controllable degradation, the product of this invention provides a direct and feasible environmentally friendly alternative for these areas with high consumption of single-use plastics, and has broad application prospects.
[0020] Compared with existing technologies, the present invention has the following advantages and beneficial effects: 1) Low cost: By using low-cost PBS as the main matrix and filling it with a large amount of modified low-cost nano-calcium carbonate, the raw material cost is significantly reduced and the product's market competitiveness is enhanced.
[0021] 2) High performance: The optimized PBS / PLA ratio, compatibilizer and nanofiller work synergistically to give the garbage bags high tensile strength, high elongation at break and high tear resistance, meeting the requirements of daily use.
[0022] 3) Easy to process: The special raw material pretreatment process and precise extrusion blow molding temperature control, combined with the internal cooling (IBC) system, effectively solve the problems of easy hydrolysis and unstable film bubbles in polyester material processing, and improve production efficiency and product yield.
[0023] 4) Controllable degradation: By adding specific degradation aids and combining them with the polyester matrix, the product's performance is ensured to be stable during its service life, while it can achieve rapid and complete biodegradation in a composting environment, making it environmentally friendly. Attached Figure Description
[0024] Figure 1 Results of mechanical property tests on garbage bags: Tensile strength (MPa) Figure 2 Results of mechanical property tests on garbage bags: Elongation at break (%) Figure 3 Results of mechanical property tests on garbage bags: Right-angle tear strength (kN / m) Figure 4 Results of biodegradation rate after 180 days. Detailed Implementation
[0025] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below. However, it should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of the invention. Furthermore, descriptions of well-known structures and technologies are omitted in the following description to avoid unnecessarily obscuring the concept of the invention. All raw materials used in the embodiments of this invention are commercially available.
[0026] Table 1 Raw Material List Polybutylene succinate (PBS) Intrinsic viscosity [η]: 1.2-1.8 dL / g The main matrix material provides toughness and biodegradability. Polylactic acid (PLA) Optical purity ≥ 96% The main matrix material provides strength and rigidity. Nano calcium carbonate Particle size D90 ≤ 2μm, surface modified with silane coupling agent Filling and reinforcing reduces costs and improves processability. Degradation aids One or a mixture of ferric stearate and cobalt stearate Accelerate and regulate the biodegradation process compatibilizer Maleic anhydride-grafted polybutylene succinate (PBS-g-MAH) Improve the compatibility of PBS and PLA and enhance mechanical properties. Opening agent Erucamide, purity ≥ 98% Prevents film adhesion and improves user experience Table 2 Instrument List Co-rotating parallel twin-screw extruder (for masterbatch granulation) TE-65 Screw diameter: 65 mm; L / D ratio: 40:1 - 48:1; Screw configuration: modular, equipped with kneading blocks and reverse thread elements for high shear and thorough mixing; Heating and cooling methods: electric heating, water cooling. Temperature settings for each zone: Zone 1: 150-160℃; Zone 2: 160-170℃; Zone 3: 170-175℃; Zone 4: 175-180℃; Zone 5: 175-180℃; Die head: 170-175℃; Screw speed: 200-350 rpm; Melt pressure: 3-6 MPa Single-screw extrusion blown film machine (for film forming) SJ-45 / 28 Screw diameter: 45 mm; Length-to-diameter ratio (L / D): 28:1; Screw type: Barrier screw, beneficial for melt homogenization and stability; Extrusion die type: Spiral mandrel type annular die; Cooling system: Standard internal cooling (IBC) system. - Example
[0027] A low-cost, biodegradable polyester plastic garbage bag, the raw materials of which include, by weight: Polybutylene succinate (PBS) 50 parts Polylactic acid (PLA) 25 parts 10 parts of nano-calcium carbonate (D90=1.5μm) surface modified with silane coupling agent KH-570. Degradation aid (ferric stearate) 0.5 parts Compatibilizer (maleic anhydride grafted PBS, PBS-g-MAH) 0.5 parts Opening agent (erucamide) 0.3 parts Its preparation process includes: (1) Raw material pretreatment and drying: PBS and PLA were vacuum dried at 85℃ for 5 hours; modified nano calcium carbonate was dried at 115℃ for 2.5 hours; (2) High-speed mixing: Add all the raw materials processed in step (1) into a high-speed mixer and mix at 1000 rpm for 10 minutes at 70°C; (3) Melt blending and extrusion: The premixed material is fed into a co-rotating parallel twin-screw extruder (L / D=44:1) for granulation. The temperature of each section is set as follows: Zone 1 155℃, Zone 2 165℃, Zone 3 172℃, Zone 4 178℃, Zone 5 178℃, Die head temperature 172℃, Screw speed 280 rpm, and melt pressure controlled at 4.5MPa. (4) Blown film forming: The masterbatch is fed into a single-screw extruder, and the temperatures are set as follows: Zone 1 152℃, Zone 2 160℃, Zone 3 168℃, Zone 4 172℃, and the die temperature is 168℃. An internal cooling (IBC) system is used, the cooling air temperature is 20℃, the blow-up ratio is 3:1, and the traction speed is 20 m / min to produce a film with a thickness of 0.020 mm. (5) Post-processing and bag making: The film is treated with corona (40 dynes / cm) and then rolled up and heat-sealed to make bags. Example
[0028] A low-cost, biodegradable polyester plastic garbage bag, the raw materials of which include, by weight: Polybutylene succinate (PBS) 60 portions Polylactic acid (PLA) 20 parts 15 parts of nano-calcium carbonate (D90=1.8μm) surface-modified with silane coupling agent KH-570. Degradation aid (cobalt stearate) 1.2 parts Compatibilizer (PBS-g-MAH) 1.2 parts Opening agent (erucamide) 0.5 parts Its preparation process includes: (1) Raw material pretreatment and drying: PBS and PLA were vacuum dried at 85℃ for 5 hours; modified nano calcium carbonate was dried at 115℃ for 2.5 hours; (2) High-speed mixing: Mix at 1000 rpm for 10 minutes at 70°C; (3) Melt blending and extrusion: Granulation was carried out using a twin-screw extruder (L / D=44:1). The temperature settings for each section were: Zone 1 155℃, Zone 2 165℃, Zone 3 172℃, Zone 4 178℃, Zone 5 178℃, Die head temperature 172℃, Screw speed 280 rpm, and melt pressure controlled at 4.5MPa. (4) Blown film forming: The temperature settings of the single-screw blown film machine are: Zone 1 152℃, Zone 2 160℃, Zone 3 168℃, Zone 4 172℃, and the die head temperature is 168℃. The IBC cooling air temperature is 20℃, the blow ratio is 3:1, and the traction speed is 20 m / min, to produce a film with a thickness of 0.020 mm; (5) Post-processing and bag making: The film is corona treated (40 dynes / cm) before bag making. Example
[0029] A low-cost, biodegradable polyester plastic garbage bag, the raw materials of which include, by weight: Polybutylene succinate (PBS) 70 parts Polylactic acid (PLA) 15 parts 20 parts of nano-calcium carbonate (D90=2.0μm) surface modified with silane coupling agent KH-570. Degradation aid (ferric stearate and cobalt stearate mixed in a 1:1 ratio) 2 parts Compatibilizer (PBS-g-MAH) 2 parts Opening agent (erucamide) 1 part Its preparation process is the same as in Example 2.
[0030] A type of plastic garbage bag, whose raw material composition and preparation process are the same as in Example 2, except that no compatibilizer (PBS-g-MAH) is added.
[0031] A plastic garbage bag, whose raw material composition and preparation process are the same as in Example 2, except that: an equal amount of ordinary light calcium carbonate (unmodified, D90=10μm) is used instead of nano-calcium carbonate modified with silane coupling agent.
[0032] A plastic garbage bag, whose raw material composition and preparation process are the same as in Example 2, except that: in the blown film forming process, the internal cooling (IBC) system is not turned on, a traditional external cooling air ring is used, and the blow ratio is adjusted to 2:1.
[0033] A plastic garbage bag, whose raw material composition and preparation process are the same as in Example 2, except that the ratio of PBS to PLA is 40:40.
[0034] A plastic garbage bag, whose raw material composition and preparation process are the same as in Example 2, the difference is that: in step (1), PBS and PLA are dried at 80°C under normal pressure for 2 hours, with a water content of about 800ppm; in step (3), the temperature of each zone of the twin-screw extruder is increased by 10°C.
[0035] A commercially available biodegradable garbage bag product based on a PLA / starch blend system.
[0036] Comparative test of mechanical properties of garbage bags Objective: To verify whether the mechanical properties of the garbage bag of the present invention meet the requirements of daily use, and to examine the synergistic effect of each component and process.
[0037] method: Sample preparation: Take the garbage bag samples prepared in Examples 1-3 and Comparative Examples 1-6, and after conditioning for 24 hours in a standard environment of (23±2)℃ and 50%±10% relative humidity, cut dumbbell-shaped specimens according to GB / T 1040.3-2006 standard.
[0038] Tensile test: Using a universal testing machine (model: Instron 3365), the tensile strength and elongation at break of the samples were determined at a tensile speed of 500 mm / min. Each sample was tested in parallel 5 times, and the average value was taken.
[0039] Right-angle tear test: According to QB / T 1130-1991 standard, the right-angle tear strength of the sample is determined. Each sample is tested in parallel 5 times and the average value is taken.
[0040] Results: See Table 3 and Figures 1-3 .
[0041] Table 3: Test Results of Mechanical Properties of Garbage Bags Example 1 22.5 320 85 Example 2 25.8 380 98 Example 3 23.1 350 90 Comparative Example 1 18.2 180 65 Comparative Example 2 16.5 150 58 Comparative Example 3 20.1 280 78 Comparative Example 4 19.7 95 62 Comparative Example 5 17.8 160 60 Comparative Example 6 15.3 50 45 Conclusion: The garbage bags of Examples 1-3 significantly outperformed the comparative examples in tensile strength, elongation at break, and right-angle tear strength. Comparative Example 1 (without compatibilizer) and Comparative Example 4 (excessive PLA ratio) showed a significant decrease in elongation at break, demonstrating the crucial role of the specific ratio of compatibilizer to PBS / PLA in maintaining material toughness. Comparative Example 2 (using ordinary calcium carbonate) exhibited the worst performance across all categories, indicating the reinforcing and compressive effect of the nano-modified filler. Example 2 demonstrated the best overall performance and met the requirements for heavy-duty garbage.
[0042] Biodegradability test Objective: To verify the biodegradability of the garbage bag of the present invention under controlled composting conditions.
[0043] method: The composting process shall be carried out according to the controlled composting method in GB / T 20197-2024 "Definition, Classification, Marking and Degradation Performance Requirements of Degradable Plastics".
[0044] The samples from each embodiment and the comparative example were ground and mixed with the inoculum (mature compost from a stabilized compost plant) and placed in a composting environment at (58±2)℃.
[0045] The amount of carbon dioxide released is measured periodically to calculate the biodegradation rate. The testing period is 180 days.
[0046] Results: See Table 4 and Figure 4 .
[0047] Table 4: Biodegradation rate results after 180 days Example 1 92.5 Example 2 95.7 Example 3 93.9 Comparative Example 1 91.1 Comparative Example 6 85.2 Conclusion: All experimental groups achieved a biodegradation rate exceeding 90% within 180 days, meeting the standard requirements. This invention, through the combination of a PBS / PLA matrix and a degradation aid, achieves rapid and complete biodegradation after use while ensuring stable performance throughout its service life.
[0048] Stability assessment of blow-molded film bubbles Objective: To evaluate the effect of the process of the present invention on improving the stability of blown film bubbles.
[0049] method: On the production line, the processes of Example 2, Comparative Example 3 (without IBC, low blow-up ratio) and Comparative Example 5 (insufficient drying, high temperature) were continuously run.
[0050] Record the number of times the membrane bubble ruptures or exhibits obvious shaking or wrinkling within a 1-hour production cycle.
[0051] Observe and record the morphological stability of membrane vesicles.
[0052] Results: See Table 5.
[0053] Table 5: Results of membrane bubble stability assessment.
[0054] Example 2 0 Stable, rounded, with minimal vibration Comparative Example 3 5 The shaking is obvious, with periodic oscillations and high instability. Comparative Example 5 >10 Frequent bubble bursting prevents continuous molding. Conclusion: The deep drying process, precise temperature control, and internal cooling (IBC) system employed in Example 2 of this invention ensure that the polyester melt has suitable strength and ductility, thereby achieving extremely high film bubble stability, which is the key to achieving high-yield and high-quality film production.
[0055] Cost Analysis Objective: To quantify the cost advantages of this invention.
[0056] method: Taking the production of 1 ton of garbage bag masterbatch as an example, the main material costs of Example 2, Comparative Example 6 (commercially available PLA / starch system), and pure PLA raw materials are statistically analyzed.
[0057] The unit price of raw materials is estimated based on the average market price: PBS (20,000 yuan / ton), PLA (25,000 yuan / ton), modified nano calcium carbonate (4,000 yuan / ton), starch (6,000 yuan / ton).
[0058] Results: See Table 6.
[0059] Table 6: Estimated Raw Material Cost Per Ton of Masterbatch Example 2 1.78 Comparative Example 6 (PLA / Starch) 2.05 Pure PLA 2.50 Conclusion: By using relatively inexpensive PBS as the main component and filling it with a large amount of low-cost functional nano-calcium carbonate, this invention significantly reduces raw material costs without sacrificing performance, and is significantly more price-competitive than commercially available biodegradable materials.
[0060] Test Case Summary: Based on the above test examples, the present invention has the following advantages: 1. Mechanical properties: The garbage bag of Example 2 has a tensile strength of 25.8 MPa, an elongation at break of 380%, and a right-angle tear strength of 98 kN / m, which are all superior to the comparative example and commercially available PLA / starch-based products (Comparative Example 6: 15.3 MPa, 50%, 45 kN / m).
[0061] 2. Degradation performance: In the 180-day controlled composting test, the biodegradation rate of Example 2 reached 95%, which meets and exceeds the relevant standard (≥90%) requirements.
[0062] 3. Processing stability: In Example 2, the membrane bubble remained stable during the production process and did not rupture within 1 hour; while in Comparative Example 3 (without IBC) and Comparative Example 5 (insufficient drying), the bubble ruptured 5 times and more than 10 times, respectively, proving that the process of the present invention is crucial for stable production.
[0063] 4. Cost Analysis: The estimated cost of the masterbatch raw material in Example 2 of this invention is approximately RMB 17,800 / ton, which is significantly lower than that of commercially available PLA / starch system (Comparative Example 6, approximately RMB 20,500 / ton) and pure PLA raw material (approximately RMB 25,000 / ton), demonstrating a clear cost advantage.
[0064] In summary, the test data demonstrate that the present invention has achieved significant technological advancements in terms of mechanical properties, degradation performance, processing stability, and cost control.
[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Therefore, any changes and modifications made to the embodiments described herein based on the innovative concept of the present invention, or equivalent structural or procedural transformations made using the content of the present invention specification, directly or indirectly applying the above technical solutions to other related technical fields, are all included within the scope of protection of the present invention patent.
Claims
1. A low-cost extrusion blow molding process for biodegradable polyester plastic garbage bags, characterized in that, Includes the following steps: (1) Raw material pretreatment and drying: 50-70 parts by weight of polybutylene succinate (PBS) and 15-25 parts by weight of polylactic acid (PLA) were vacuum dried at 80-90℃ for 4-6 hours to reduce the moisture content of the material to below 200ppm; 10-20 parts by weight of nano-sized calcium carbonate with a particle size D90 ≤ 2μm that has been surface modified with silane coupling agent were dried at 110-120℃ for 2-3 hours for later use. (2) High-speed mixing: The dried PBS and PLA from step (1), modified nano-calcium carbonate, 0.5-2 parts by weight of transition metal salt compound as degradation aid, 0.5-2 parts by weight of maleic anhydride grafted polyester as compatibilizer, and 0.3-1 parts by weight of erucic acid amide opening agent are added to a high-speed mixer and mixed at 800-1200 rpm for 8-15 minutes at 60-80℃ to obtain a premixed uniform material; (3) Melt blending and extrusion: The premixed material obtained in step (2) is fed into a co-rotating parallel twin-screw extruder through a loss-in-weight feeder for melt blending and granulation. The temperature settings of each section of the twin-screw extruder from the feed port to the die head are as follows: Zone 1 150-160℃, Zone 2 160-170℃, Zone 3 170-175℃, Zone 4 175-180℃, Zone 5 175-180℃, the die head temperature is 170-175℃, the screw speed is 200-350 rpm, and the melt pressure is controlled at 3-6 MPa. After water cooling and pelletizing, biodegradable plastic masterbatch is obtained. (4) Blown film forming: The biodegradable plastic masterbatch obtained in step (3) is fed into a single-screw extruder blown film machine. The temperature of the single-screw extruder is set as follows: Zone 1 150-155℃, Zone 2 155-165℃, Zone 3 165-170℃, Zone 4 170-175℃, and the die temperature is 165-170℃. The melt is extruded through the annular die to form a tubular blank. Cooling air at 15-25℃ is injected into the film bubble. The film bubble inflation ratio is 2.5:1-3.5:1, and the traction speed is 15-25 m / min, thereby preparing a blown film with a thickness of 0.015-0.025 mm. (5) Post-processing and bag making: The blown film obtained in step (4) is stretched, flattened and corona treated. After the treatment strength is ≥38 dynes / cm, it is rolled into a film roll. Finally, the film roll is cut, heat-sealed and punched by a heat-sealing bag making machine to make the low-cost polyester biodegradable plastic garbage bag.
2. The extrusion blow molding process according to claim 1, characterized in that, The weight ratio of polybutylene succinate (PBS) to polylactic acid (PLA) in step (1) is 60:
20.
3. The extrusion blow molding process according to claim 1, characterized in that, The transition metal salt degradation aid mentioned in step (2) is one or a mixture of two of iron stearate and cobalt stearate; the compatibilizer is maleic anhydride grafted polybutylene succinate PBS-g-MAH.
4. The extrusion blow molding process according to claim 1, characterized in that, The amount of erucamide-based opening agent added in step (2) is 0.5 parts by weight.
5. The extrusion blow molding process according to claim 1, characterized in that, The screw length-to-diameter ratio (L / D) of the twin-screw extruder described in step (3) is 40:1-48:
1.
6. The extrusion blow molding process according to claim 1, characterized in that, The blown film ratio in step (4) is 3:1, and the thickness of the blown film is 0.020 mm.
7. A low-cost polyester biodegradable plastic garbage bag, characterized in that, It is prepared by any one of the extrusion blow molding processes according to claims 1 to 6.
8. The low-cost polyester biodegradable plastic garbage bag according to claim 7, characterized in that, The garbage bag has a tensile strength ≥20MPa, an elongation at break ≥300%, and a right-angle tear strength ≥80kN / m.
9. The application of the low-cost polyester biodegradable plastic garbage bag as described in claim 7 in the collection of household waste, supermarket shopping, or temporary covering of agricultural waste.
Citation Information
Patent Citations
PBS (polybuthylenesuccinate) fully biodegradable material as well as preparation method and application thereof
CN103709688A
Biodegradable PLA modified material with high heat resistance and high toughness and preparation method thereof
CN113045872A